The march of pluripotent stem cells in cardiovascular regenerative medicine - Abou-Saleh, H.; Zouein, F. A.; El-Yazbi, A.; Sanoudou, D.; Raynaud, C.; Rao, C.; Pintus, G.; Dehaini, H.; Eid, A. H. (Stem Cell Res TherStem Cell Res TherStem Cell Res Ther, 2018)
Cardiovascular disease (CVD) continues to be the leading cause of global morbidity and mortality. Heart failure remains a major contributor to this mortality. Despite major therapeutic advances over the past decades, a better understanding of molecular and cellular mechanisms of CVD as well as improved therapeutic strategies for the management or treatment of heart failure are increasingly needed. Loss of myocardium is a major driver of heart failure. An attractive approach that appears to provide promising results in reducing cardiac degeneration is stem cell therapy (SCT). In this review, we describe different types of stem cells, including embryonic and adult stem cells, and we provide a detailed discussion of the properties of induced pluripotent stem cells (iPSCs). We also present and critically discuss the key methods used for converting somatic cells to pluripotent cells and iPSCs to cardiomyocytes (CMs), along with their advantages and limitations. Integrating and non-integrating reprogramming methods as well as characterization of iPSCs and iPSC-derived CMs are discussed. Furthermore, we critically present various methods of differentiating iPSCs to CMs. The value of iPSC-CMs in regenerative medicine as well as myocardial disease modeling and cardiac regeneration are emphasized.
Abou-Saleh, HaissamZouein, Fouad AEl-Yazbi, AhmedSanoudou, DespinaRaynaud, ChristopheRao, ChristopherPintus, GianfrancoDehaini, HassanEid, Ali HengResearch Support, Non-U.S. Gov'tReviewEngland2018/07/29 06:00Stem Cell Res Ther. 2018 Jul 27;9(1):201. doi: 10.1186/s13287-018-0947-5.
Keywords: Cardiovascular Diseases/*genetics; Cell Differentiation; Cell- and Tissue-Based Therapy/*methods; Humans; Myocytes, Cardiac/*metabolism; Pluripotent Stem Cells/metabolism; Regenerative Medicine/*methods